Distribution of Dissolved Nitrogen Compounds in the Water Column of a Meromictic Subarctic Lake - Taisiya Ya. Vorobyeva; Anna A. Chupakova; Artem V. Chupakov; Svetlana A. Zabelina; Olga Y. Moreva; Oleg S. Pokrovsky (Nitrogen, 2021)
In order to better understand the biogeochemical cycle of nitrogen in meromictic lakes, which can serve as a model for past aquatic environments, we measured dissolved concentrations of nitrate, nitrite, ammonium, and organic nitrogen in the deep (39 m maximal depth) subarctic Lake Svetloe (NW Russia). The lake is a rare type of freshwater meromictic water body with high concentrations of methane, ferrous iron, and manganese and low concentrations of sulfates and sulfides in the monimolimnion. In the oligotrophic mixolimnion, the concentration of mineral forms of nitrogen decreased in summer compared to winter, likely due to a phytoplankton bloom. The decomposition of the bulk of the organic matter occurs under microaerophilic/anaerobic conditions of the chemocline and is accompanied by the accumulation of nitrogen in the form of N-NH4 in the monimolimnion. We revealed a strong relationship between methane and nitrogen cycles in the chemocline and monimolimnion horizons. The nitrate concentrations in Lake Svetloe varied from 9 to 13 μM throughout the water column. This fact is rare for meromictic lakes, where nitrate concentrations up to 13 µM are found in the monimolimnion zone down to the bottom layers. We hypothesize, in accord with available data for other stratified lakes that under conditions of high concentrations of manganese and ammonium at the boundary of redox conditions and below, anaerobic nitrification with the formation of nitrate occurs. Overall, most of the organic matter in Lake Svetloe undergoes biodegradation essentially under microaerophilic/anaerobic conditions of the chemocline and the monimolimnion. Consequently, the manifestation of the biogeochemical nitrogen cycle is expressed in these horizons in the most vivid and complex relationship with other cycles of elements.